Urban Food Production: A Contribution to the Fulfillment of the Sdgs. An Experience from University Social Projection - Estupiñán Aponte, Luis Carlos (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The current food crisis is one of the most severe in recent history. It is caused by various factors, including climate change, soil degradation, and the concentration of the human population in urban centers. In many regions of the world, the urban population exceeds 80% of the rural population, and this trend is on the rise. In urban areas, access to food depends primarily on purchasing power. Therefore, high rates of unemployment or underemployment, along with the high cost of food and increasing family expenses such as rent, transportation, and public services, reduce the resources available to buy food. This creates a high degree of food vulnerability, particularly for families in a situation of socioeconomic marginality, such as women and children. According to the 2023 SOFI report presented by FAO, over 122 million people face hunger daily. Urban and peri-urban agriculture is emerging as a potential solution for producing safe food. While it is not a comprehensive solution to this issue, it is a viable option. To achieve this, the project applies principles of the circular economy by utilizing available resources for both space and materials in the assembly of the gardens. Additionally, plant waste is processed to produce fertilizers, and agroecological principles are employed for production, such as planting a high diversity of vegetable, aromatic, and condiment species in the same space. The distribution of plants is also carefully considered, taking into account their differential requirements for luminosity and relative humidity. In summary, the direction of production for phytosanitary management involves the application of botanical and microbiological controls. The creation of urban gardens is characterized by broad community participation, knowledge exchange, and the promotion of meeting and recreation spaces. These elements serve as mechanisms for the reconstruction of the social fabric, which is a basic element for building conditions of food and nutrition security.